European dermatology forum – updated guidelines on the use of extracorporeal photopheresis 2020 – part 1. (6th October 2020) - Knobler, R.; Arenberger, P.; Arun, A.; Assaf, C.; Bagot, M.; Berlin, G.; Bohbot, A.; Calzavara‐Pinton, P.; Child, F.; Cho, A.; French, L.E.; Gennery, A.R.; et al.
Abstract: Background: Following the first investigational study on the use of extracorporeal photopheresis for the treatment of cutaneous T‐cell lymphoma published in 1983, this technology has received continued use and further recognition for additional earlier as well as refractory forms. After the publication of the first guidelines for this technology in the JEADV in 2014, this technology has maintained additional promise in the treatment of other severe and refractory conditions in a multi‐disciplinary setting. It has confirmed recognition in well‐known documented conditions such as graft‐versus‐host disease after allogeneic bone marrow transplantation, systemic sclerosis, solid organ transplant rejection including lung, heart and liver and to a lesser extent inflammatory bowel disease. Materials and methods: In order to further provide recognized expert practical guidelines for the use of this technology for all indications, the European Dermatology Forum (EDF) again proceeded to address these questions in the hands of the recognized experts within and outside the field of dermatology. This was done using the recognized and approved guidelines of EDF for this task. All authors had the opportunity to review each contribution as it was added. Results and conclusion: These updated 2020 guidelines provide at present the most comprehensive available expert recommendations for the use of extracorporeal photopheresis based on the available published literature and expert consensus opinion. The guidelines are divided in two parts: PART I covers cutaneous T‐cell lymphoma, chronic graft‐versus‐host disease and acute graft‐versus‐host disease while PART II will cover scleroderma, solid organ transplantation, Crohn's disease, use of ECP in paediatrics practice, atopic dermatitis, type 1 diabetes, pemphigus, epidermolysis bullosa acquisita and erosive oral lichen planus.